-38=x+(-27)

Simple and best practice solution for -38=x+(-27) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -38=x+(-27) equation:



-38=x+(-27)
We move all terms to the left:
-38-(x+(-27))=0
We calculate terms in parentheses: -(x+(-27)), so:
x+(-27)
We add all the numbers together, and all the variables
x-27
Back to the equation:
-(x-27)
We get rid of parentheses
-x+27-38=0
We add all the numbers together, and all the variables
-1x-11=0
We move all terms containing x to the left, all other terms to the right
-x=11
x=11/-1
x=-11

See similar equations:

| 5(x+3)+2x=-6 | | 8x+12x=280 | | W(3n)=12n+2 | | 3x/2-1x=1 | | 5/3+3m/8=55/24 | | 8+2x=280 | | w(-8)=4X+5 | | 7b-b+14=5b+3b | | 6(n-2)^2=864 | | 6x+4=-11x | | 3x+2=4+x+(1+2x) | | 8(x)+6(2x)=280 | | 4(3+c)=c=c+4 | | 8(x)+6(x)=280 | | 1/5^x^2-8=5^4 | | 23x+17+18x-1=180 | | x/7-3=9/14 | | 4x=4+2x+4 | | -(-x)x=46 | | -5x-10=2-(x+4 | | 1/5^x^2-8=625 | | 9x+2+6-x=10 | | 3x-5(3x+9)=27 | | 25x^2-55x+25=0 | | 4x+8=5× | | 9x+4=6+4 | | 0.14(y-8)+0.16y=0.10y-2.1= | | 3.4=9.7-0.9x | | 8-1+3y=44 | | 9x+4=6+9x | | 12y+6=6(2y+10 | | 60+42.95x=25+49x |

Equations solver categories